1971
DOI: 10.1161/01.cir.44.1.59
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Sino-atrial Node Function in Man by Overdrive Suppression

Abstract: Sino-atrial node (SAN) function was evaluated in 46 patients, three of whom had the sick sinus syndrome. Patients were paced from the right atrium for 15 to 180 sec at rates of 90, 110, 130, and 150 beats/min. The rapid cessation of pacing was associated with suppression of the SAN at all paced rates and at all durations of pacing. The observed pause was terminated by a sinus beat in all instances. The duration of pacing had little influence on the duration of the observed pause. The pause increased as the pac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
73
1

Year Published

1974
1974
1997
1997

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 379 publications
(80 citation statements)
references
References 19 publications
4
73
1
Order By: Relevance
“…Atrial, atrioventricular, and ventricular conduction properties were all assessed in wild-type and ␣MHC 403/ϩ mice. Sinus node function was evaluated by measuring the ratecorrected sinus node recovery time (CSNRT) (12). Representative three-channel recordings of surface, atrial, and ventricular intracardiac electrograms for wild-type and ␣MHC 403/ϩ mice are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Atrial, atrioventricular, and ventricular conduction properties were all assessed in wild-type and ␣MHC 403/ϩ mice. Sinus node function was evaluated by measuring the ratecorrected sinus node recovery time (CSNRT) (12). Representative three-channel recordings of surface, atrial, and ventricular intracardiac electrograms for wild-type and ␣MHC 403/ϩ mice are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The sinus node function was evaluated by measuring sinus node recovery time (SNRT) at two pacing drive rates, including corrected SNRT (SNRT less the sinus cycle length [SCL]) and SNRT/SCL percentage (6,12). Atrioventricular (A-V) conduction properties were assessed with rapid atrial pacing at rates up to 1,200 bpm.…”
Section: Methodsmentioning
confidence: 99%
“…Other authors have reported success rates from 36% (Vogel, Desoutter, Bellanger, Motte & Wesli, 1976) to 69% (Valere, Guerot, Fenoy, Branvin, Urbanczyk & Tricot, 1977 (Sasyniuk & Kus, 1976) its anticholinergic effect tends to prevent slowing of sinus node discharge (Birkhead & Vaughan-Williams, 1977). Initial observations (Befeler et al, 1975) showed that disopyramide does not prolong and may shorten sinus node recovery time following overdrive suppression (Mandel, Hayakawa, Danzig & Marcus, 1971). More recent studies have confirmed these results in patients with normal sinus node function but have suggested that the compromised sinus node may be depressed by disopyramide (Reid, Williams & Parashar, 1977).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, SN recovery time (SNRT) and sinoatrial conduction time (SACT) have been proposed as adjunctive diagnostic tools. [2][3][4][5] Although electrophysiologic testing of the SN has been clinically valuable, it lacks a high degree of specificity and sensitivity,' 7 and autonomic influences can significantly alter SN function.8'" Accordingly, electrophysiologic testing of SN function may be greatly limited without a consideration of these factors.…”
mentioning
confidence: 99%